2020
DOI: 10.1111/jocd.13860
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin‐1, RIP1/RIP3 inhibitor, relieves transforming growth factor β‐induced wound‐healing process in formation of hypertrophic scars

Abstract: Background Hypertrophic scars (HS) are common pathologic processes emerged during wound‐healing process. The receptor‐interacting protein kinase (RIP) might participate in keloid formation. Aims This study aimed to investigate Necrostatin‐1 (Nec‐1), a RIP1/RIP3 inhibitor, in the formation of hypertrophic scar. Methods Human hypertrophic scar fibroblasts (HSF) were extracted from patients with hypertrophic scar. Transforming growth factor‐β1 (TGF‐β1) was performed to induce wound‐healing process including cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…KD is characterized excessive collagen deposition due to an imbalance between the production and degradation of the ECM. 12 In the process of KD tissue proliferation, the synthesis of type I and III collagens increases from the translation stage to the protein synthesis stage. It has been suggested that a large number of fibroblasts activate type I and III procollagen mRNA expression in the endoplasmic reticulum to produce type I and III procollagens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KD is characterized excessive collagen deposition due to an imbalance between the production and degradation of the ECM. 12 In the process of KD tissue proliferation, the synthesis of type I and III collagens increases from the translation stage to the protein synthesis stage. It has been suggested that a large number of fibroblasts activate type I and III procollagen mRNA expression in the endoplasmic reticulum to produce type I and III procollagens.…”
Section: Discussionmentioning
confidence: 99%
“…KD is characterized by excessive collagen deposition due to an imbalance between the production and degradation of the ECM 12 . In the process of KD tissue proliferation, the synthesis of type I and III collagens increases from the translation stage to the protein synthesis stage.…”
Section: Discussionmentioning
confidence: 99%
“… 15 A recent investigation manifested that RIPK1 was overexpressed in human hypertrophic scar fibroblasts, and inhibition of RIPK1 by using its inhibitor Necrostatin-1 partially limited proliferation and migration of the hypertrophic scar fibroblasts. 30 An in vitro and in vivo exploration from Mou and colleagues also indicated that Necrostatin-1, inhibitor of RIPK1, weakened proliferative ability of pulmonary fibroblasts, suppressed the expression of collagen I, collagen IV, α-smooth muscle actin and fibronectin, decreased collagen deposition and ameliorated fibrosis of lung tissues. 31 Combined with our research, these findings suggested that RIPK1 might promote proliferation of KFs and increase extracellular matrix in keloid.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it is also documented that a variety of drugs can downregulate necroptosis including small molecule inhibitors, immunosuppressive drugs, traditional Chinese medicines drugs, and other agents. There were plenty of small molecule inhibitors used in the treatment of multiple diseases or research in healthy subjects such as Dabrafenib, 204 Carfilzomib, 205 Sorafenib, 206 Pazopanib, 207 Ponatinib, 208 ZYZ‐803, 209 Nec‐1, 210 GSK2982772, 211 GSK3145095, 212 NSA, 63 , 64 GSK074, 76 and GW806742X. 87 The immunosuppressive drug Cyclosporine A 213 and Rapamycin 214 were also used to downregulate necroptosis.…”
Section: Drugs and Agents That Regulate Necroptosismentioning
confidence: 99%